Red dragon fruit (Hylocereus costaricensis Britt. Et R.) peel extract as a natural dye alternative in microscopic observation of plant tissues: The practical guide in senior high school - Wagiyanti, Heni; Noor, Rasuane (University of Muhammadiyah Malang, 2017)
Prepared slide of plant tissue needs to be staining to facilitate observations under microscope. Laboratorium activities in schools usually use synthetic dyes which expensive and can be damaged the student. Therefore the exploration of alternative dyes need to be established, such as utilizing of red dragon fruit (Hylocereus castaricensis Britt. Et R.). This study aims to (1) find out the best concentration of dragon fruit peel extract for staining plant tissue prepared slide and (2) to develop the practical guide related to plant tissue observation. The qualitative research used different concentration Â of red dragon fruit peel extract, namely: 30%, 40%, 50%, 60%, 70%, 80%, 90%, and 100% with 3 repetitions. Data were obtained from observation photos of prepared slide. The result showed that the most contrast prepared slide was used red dragon fruit extract in 60% concentration. The result use to arrange practical guide in observation of plant tissues which is validated by material expert. The validation result showed âvery goodâ criteria (86.01%).